Microdifferential Pressure Measurement Device for Cellular Microenvironments - Mami Akaike; Jun Hatakeyama; Yoichi Saito; Yoshitaka Nakanishi; Kenji Shimamura; Yuta Nakashima (Bioengineering)
Mechanical forces influence cellular proliferation, differentiation, tissue morphogenesis, and functional expression within the body. To comprehend the impact of these forces on living organisms, their quantification is essential. This study introduces a novel microdifferential pressure measurement device tailored for cellular-scale pressure assessments. The device comprises a glass substrate and a microchannel constructed of polydimethylsiloxane, polytetrafluoroethylene tubes, a glass capillary, and a microsyringe pump. This device obviates the need for electrical measurements, relying solely on the displacement of ultrapure water within the microchannel to assess the micropressure in embryos. First, the device was subjected to arbitrary pressures, and the relationship between the pressure and the displacement of ultrapure water in the microchannel was determined. Calibration results showed that the displacement dx [μm] could be calculated from the pressure P [Pa] using the equation dx = 0.36 P. The coefficient of determination was shown to be 0.87, indicating a linear response. When utilized to measure brain ventricular pressure in mouse embryos, the fabricated device yielded an average pressure reading of 1313 ± 640 Pa. This device can facilitate the measurement of pressure within microcavities in living tissues and other areas requiring precise and localized pressure evaluations.